Role of neonatal hearing screening programme in the auditory rehabilitation of children - Araújo-Martins, J. (2015)
Objectives: To determine the influence of the implementation of universal newborn hearing screening programs in the referral to an auditory rehabilitation clinic.Methods: Setting – auditory rehabilitation clinic in a tertiary referral centre in Lisbon. Study design – observational, retrospective cohort study based on patient clinical records. Population – all records of children born 1998 and after (437 in total) were analysed and 322 meeting inclusion criteria were selected.Results: Mean age of referral to our clinic has steadily declined from 55 months (1998-2000) to 12 months (2007-2009). About 3/4 of patients are referred due to hearing loss or neonatal screening results.Conclusion: The neonatal universal screening program has allowed earlier referral of hearing impaired children to an auditory rehabilitation clinic. It’s important to keep those programs running to ensure the early rehabilitation of these children.